Inhibition of NLRP3 inflammasome by glibenclamide attenuated dopaminergic neurodegeneration and motor deficits in paraquat and maneb-induced mouse Parkinson's disease model. (1st October 2021) - Qiu, Xiaofei; Wang, Qinghui; Hou, Liyan; Zhang, Cuili; Wang, Qingshan; Zhao, Xiulan
Highlights: Glibenclamide protected dopaminergic neurons in paraquat and maneb-intoxicated mice. Glibenclamide attenuated paraquat and maneb-induced NLRP3 inflammasome activation. Glibenclamide suppressed paraquat and maneb-induced microglial activation and M1 polarization. Glibenclamide suppressed paraquat and maneb-induced oxidative damage via iNOS and NOX2. Abstract: Pesticides exposure can lead to damage of dopaminergic neurons, which are associated with increased risk of Parkinson's disease (PD). However, the etiology of PD remains poorly understood and no therapeutic strategy is available. Previous studies suggested the involvement of NLRP3 inflammasome in the onset of PD. This study was designed to investigate whether glibenclamide, an inhibitor of NLRP3 inflammasome, could offer a reliable protective strategy for PD in a mouse PD model induced by paraquat and maneb. We found that glibenclamide exerted potent neuroprotection against paraquat and maneb-induced upregulation of α-synuclein, dopaminergic neurodegeneration and motor impairment in brain of mice. Mechanistically, glibenclamide treatment blocked NLRP3 inflammasome activation evidenced by reduced expressions of NLRP3, activated caspase-1 and mature interleukin-1β in glibenclamide co-treated mice compared with those in paraquat and maneb group mice. Furthermore, glibenclamide treatment mitigated paraquat and maneb-induced microglial M1 proinflammatory response and nuclear factor-κB activation in mice. Finally, the increased superoxide production, lipid peroxidation, protein levels of NADPH oxidase 2 (NOX2) and inducible nitric oxide synthase (iNOS) induced by paraquat and maneb were all attenuated by glibenclamide. Overall, our findings demonstrated that glibenclamide protected dopaminergic neurons in a mouse PD model induced by combined exposures of paraquat and maneb through suppression of NLRP3 inflammasome activation, microglial M1 polarization and oxidative stress.